2020
DOI: 10.1177/0192513x19894369
|View full text |Cite
|
Sign up to set email alerts
|

Mothers, Fathers, Daughters, and Sons: Gender Differences in Adults’ Intergenerational Ties

Abstract: Women are more involved in family ties than men, but these differences may vary across generations as gender roles have shifted. We know little about gender patterns across generations in the same family, however. To address this gap, midlife men and women aged 40–60 ( n = 633) from the Family Exchanges Study reported on relationships with each aging parent and each grown child. Mothers were more involved (e.g., more frequent contact, greater positive and negative relationship qualities, and more frequent supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 70 publications
3
52
0
1
Order By: Relevance
“…These patterns of support are also conditioned on gender. A vast literature has shown that daughters play a central role in the matrilineal Western cultures (Fingerman, Huo, & Birditt, ; Suitor & Pillemer, ; Suitor, Pillemer, & Sechrist, ). In Asian countries (e.g., China, Korea, Japan), by contrast, the dominant patrilineal norm renders parents more willing to help their sons and expect sons to reciprocate (Hu, ; Kim, Zarit, Fingerman, & Han, ).…”
Section: A Recession Financial Difficulties and Other Problems Adulmentioning
confidence: 99%
“…These patterns of support are also conditioned on gender. A vast literature has shown that daughters play a central role in the matrilineal Western cultures (Fingerman, Huo, & Birditt, ; Suitor & Pillemer, ; Suitor, Pillemer, & Sechrist, ). In Asian countries (e.g., China, Korea, Japan), by contrast, the dominant patrilineal norm renders parents more willing to help their sons and expect sons to reciprocate (Hu, ; Kim, Zarit, Fingerman, & Han, ).…”
Section: A Recession Financial Difficulties and Other Problems Adulmentioning
confidence: 99%
“…Ambivalence in these relationships appears to be fueled by a specific form of oscillation between dependency and autonomy among parents and grandparents, which results in tensions between involvement and interference (Connidis, 2015;Fingerman et al, 2004;Lüscher, 2002). Many studies have focused on grandparents' feelings of ambivalence (e.g., Girardin et al, 2018;Lüscher & Lettke, 2004;Neuberger & Haberkern, 2014;Pillemer & Suitor, 2002;Pillemer et al, 2007Pillemer et al, , 2012, while some have also included the parents' perspectives (e.g., Ferring et al, 2009;Fingerman et al, 2020;Gilligan et al, 2015a;Willson et al, 2003). These studies have shown that feelings of ambivalence are perceived as stressful and can have a negative impact on relationship quality, as well as detrimental consequences for the psychological well-being of both grandparents and adult children.…”
Section: Grandparental Involvement and Intergenerational Ambivalencementioning
confidence: 99%
“…Furthermore, grandparental involvement is shaped by structural factors, i.e., the level tends to be higher in settings where female labor force participation is low, welfare state policies provide inadequate formal childcare services, and public investments in childcare infrastructures are meager (Adam et al, 2014; Bordone et al, 2017; Jappens & van Bavel, 2012). Overall, grandmothers, especially maternal grandmothers, provide larger shares of grandchild care than grandfathers (Barnett et al, 2010; Fingerman et al, 2020).…”
Section: Grandparental Involvement and Intergenerational Ambivalencementioning
confidence: 99%
See 2 more Smart Citations